A Great Place To Work. How Best Workplaces Affect How Senior Women Perceive Inclusion and Fairness - Perrin, Thibault; Vuilmet, Angélique (Relations industrielles / Industrial Relations, 2025)
In this research, we investigated how senior women perceive working in workplaces that have received the Great Place to Work® label in France, compared to those in other workplaces. Our data came from the anonymous Trust Index© survey of 346,516 respondents from 418 organizations. We used hierarchical linear regression to examine the impact of work in such workplaces on perceptions of inclusion and fairness, as a function of respondent age and gender. Our findings, compared to those reported by Carberry and Meyers (2017) for the United States, suggest that best workplaces may influence these perceptions more strongly in France. While this award serves as a barrier against the sexist double standard of aging, it has a limited effect on how senior women perceive inclusion. Our research contributes to contemporary social exchange theory on intra-organizational social structuration based on age and gender. We suggest that employment branding labels should consider demographic characteristics prior to promoting a workplace as fair and inclusive for all employees, especially in the case of senior women in France.